Strategi Digital Shopee Meningkatkan Loyalitas Pelanggan Fashion Melalui Kesadaran Merek Sebagai Mediator - Setiadi, Sandi; Maulana, Rizky; Fathussyaadah, Eva (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the effect of digital marketing and product quality on customer loyalty with brand awareness as a mediating variable in the fashion industry on the Shopee platform. The research method used is a quantitative approach with purposive sampling technique, involving 100 fashion customer respondents in Sukabumi. Hypothesis testing was carried out using the Structural Equation Modeling (SEM) method with SmartPLS 3. The results showed that product quality has a positive and significant effect on brand awareness, which in turn has a positive impact on customer loyalty. However, digital marketing has no significant direct influence on brand awareness or customer loyalty. In addition, brand awareness was shown to significantly mediate the relationship between product quality and customer loyalty. The managerial implications of these findings suggest that fashion companies on Shopee need to focus more on improving product quality to build strong brand awareness, which will ultimately increase customer loyalty. Digital marketing strategies remain relevant as support, but are not a dominant factor in shaping loyalty in the absence of solid brand awareness.